A emergência da noção de comportamento simbólico em neuropsicopatologia - Verissimo, Danilo Saretta [UNESP] (My University, 2011)
In this article, we present the notion of symbolic behavior in accordance with neuropsychopathology research from the first decades of the past century, carried out particularly in the context of aphasia research. The guiding axis was the presence of this notion in the first work by Merleau-Ponty, The structure of behavior. Based on research by Gelb and Goldstein, the philosopher takes ownership of the semantics of the symbolic and characterizes human corporality based on its capacity to move beyond the immediate nature of the experienced situations. We also show that the circumscription of symbolic behavior was conditioned by theoretical-methodological changes that permitted the passage from localizationist conceptions to globalist attitudes in view of pathological events of cerebral origin.
The emergence of the notion of symbolic behavior in neuropsychopathology
Keywords: Aphasia; Categorial attitude; Merleau-Ponty; Symbolic function